Evidence of the camera perspective bias in authentic videotaped interrogations: implications for emerging reform in the criminal justice system - Lassiter, G. Daniel (Legal and criminological psychology, 2009)
Objective. Numerous previous experiments have established the existence of a camera perspective bias in evaluations of videotaped interrogations/confessions: videotapes that make the suspect more visually conspicuous than the interrogator(s) by virtue of focusing the camera on the suspect yield assessments of voluntariness and judgments of guilt that are greater than those found when alternative presentation formats are used. One limitation of this body of research is that all the interrogations/confessions used to date were simulations; therefore, no evidence currently demonstrates that the camera perspective bias importantly generalizes to authentic videotapes recorded by police and depicting actual suspects and interrogators. Two experiments addressed this issue. Methods. Experiment 1 compared judgments of voluntariness based on viewing two authentic videotaped confessions - one recorded with the camera focused on the suspect, the other with the camera focused equally on the suspect and interrogator - with those based on listening only to the audio or reading only a transcript. Experiment 2 compared judgments of voluntariness and guilt of an originally equal-focus videotaped confession that was edited to produce suspect-focus and interrogator-focus versions. Results. In Experiment 1, participants judged the videotape version of the confession to be more voluntary than either the audio only or transcript versions, but only for the suspect-focus videotape. In Experiment 2, participants viewing the suspect-focus version of the confession (relative to the interrogator-focus version) judged it to be more voluntary and the suspect more likely to be guilty. Conclusion. The present research further strengthens the policy implications of the literature on camera perspective bias by providing evidence that the bias manifests with authentic interrogations/confessions as well as with simulations.